Assessing CREMAs’ Capacity to Govern Landscape Resources in the Western Wildlife Corridor of Northern Ghana - Eric Rega Christophe Bayala; Mathurin Zida; Kwabena Owusu Asubonteng; Mirjam A. F. Ros-Tonen; James Reed; Freddie Sayi Siangulube; Amy Ickowitz; Houria Djoudi; Terry Sunderland (Environmental Management, 2025)
Ghana initiated community resource management areas (CREMAs) as a community-based natural management approach to give local communities the right and power to manage natural resources within their territorial boundaries. The expectation is that communities and their environment would prosper through more equitable landscape governance and sustainable use of natural resources. However, the challenges to achieving full functionality of CREMA and expected results, particularly in the Western Wildlife Corridor in northern Ghana, raise questions about the governance actors’ capacity. Therefore, this study aims to assess the capacity of actors to take ownership of and lead the governance processes implied by the CREMA approach. Based on focus group discussions and individual interviews, we found that the capacities of the CREMA governance bodies are weak to implement the CREMA approach effectively. The lack of knowledge and technical skills to support multi-actor processes, the weak collaboration between actors, and the lack of sustainable financial inflows and livelihood support are key challenges to be addressed for better CREMA performance. Despite these constraints, local actors’ enthusiasm and willingness to engage more actively in the governance of their landscape constitute an opportunity for an improved implementation of the CREMA approach. We suggest that initiatives to strengthen the technical and financial capacities of governance bodies and raise awareness among the local population are necessary to improve the functioning and performance of CREMAs. In addition, actions to improve the livelihoods of local communities will enhance the mobilization and engagement of social groups in the implementation of the CREMA concept.

From conflict to collaboration through inclusive landscape governance: Evidence from a contested landscape in Ghana - James Reed; Mirjam A.F. Ros-Tonen; Samuel Adeyanju; Abdul Wahid Arimiyaw; Kwabena Asubonteng; Bernard N. Baatuwie; Eric R.C. Bayala; Damian Tom-Dery; Amy Ickowitz; Yakubu B. Issaka; Kaala B. Moombe; Joseph Mumuni; et al. (Global Environmental Change, 2024)

Trees as brokers in social networks: Cascades of rights and benefits from a Cultural Keystone Species - Houria Djoudi; Bruno Locatelli; Catherine Pehou; Matthew J. Colloff; Marlène Elias; Denis Gautier; Russell Gorddard; Barbara Vinceti; Mathurin Zida (Ambio, 2022)
Indigenous trees play key roles in West African landscapes, such as the néré tree ( Parkia biglobosa (Jacq.) R.Br. ex G.Don). We applied social–ecological network analysis to understand the social–ecological interactions around néré. We documented the benefits néré provides and the multiple social interactions it creates amongst a large range of actors. The flows of rights over the trees and benefits from them formed two hierarchical networks, or cascades, with different actors at the top. The two forms of power revealed by the two cascades of rights and benefits suggest possible powers and counter-powers across gender, ethnicity, and age. We documented how the tree catalyses social interactions across diverse groups to sustain vital social connections, and co-constitute places, culture, and relationships. We argue that a paradigm shift is urgently needed to leverage the remarkable untapped potential of indigenous trees and Cultural Keystone Species in current global restoration and climate change agendas.